The Psychometric Properties of Persian Version of Child Sensory Profile-2 in Children with Cerebral Palsy: Psychometric Properties of Persian Version of CSP-2 in Children with CP - pashmdarfard, marzieh; Rasouli Osalo , Sama; Mirzakahni Araghi, Navid; amini, malek; Dunn, Winnie (Iranian Journal of Child Neurology, 2025)
Objectives: The focus on children with cerebral palsy (CP) has mostly been on its postural, balance, and movement constraints. However, another factor that affects children’s daily functioning the manifestation of sensory processing irregularities and disorders. A standard tool can provide in-depth insight into sensory processing in children with CP by appropriately addressing their sensory issues. Materials & Methods: In this cross-sectional study, 143 children with CP participated to measure the reliability and validity of the Persian version of the Child Sensory Profile-2 (CSP-2) in children with CP. Data were collected using the Persian version of CSP-2 (parent/caregiver form) and analyzed using SPSS-26 software. Results: The current study revealed that Persian version of CSP-2 has good divergent validity in children with CP (p<0.001) as children with CP showed significantly different sensory processing patterns compared to typically developing peers, with higher scores across most subscales including Sensitivity (r = –0.61), Avoiding (r = –0.33), Registration (r = –0.21), and Seeking (r = –0.42). Excellent internal consistency showed that all items are internally consistent and reliable (0.78≤α≤ 0.91). The Intraclass Correlation Coefficient (ICC) that was used to measure test-retest reliability also confirmed its test-retest reliability (0.84≤ICC≤0.96). Conclusion: The Persian version of the CSP-2 can efficiently differentiate sensory processing patterns, sensation, and behavioral areas between typically developing children and children with CP. The excellent internal consistency and reproducibility of results in test-retests indicate that the Persian version of the CSP-2 is a valid and reliable tool to assess sensory processing in children with CP.